Effect of Third-Generation Beta Blockers on Weight Loss in a Population of Overweight-Obese Subjects in a Controlled Dietary Regimen - Maria Alessandra Gammone; Konstantinos Efthymakis; Nicolantonio D’Orazio (Journal of Nutrition and Metabolism)
Background. Overweight and obesity often develop in individuals with genetic susceptibility and concomitant risk factors; however, medications can represent precipitating factors in some cases: evidence suggests that some antihypertensive drugs can adversely affect energy homeostasis and metabolism. Aim. The primary aim of this study was to investigate whether long-term therapy with a beta blocker impairs weight loss during a period of appropriate personalized hypocaloric diet and standardized physical activity in overweight and obese hypertensive patients in monotherapy and without comorbidities, compared to other antihypertensive drugs and to a control group not taking antihypertensive therapy. Subjects and Methods. We enrolled overweight and obese patients taking antihypertensive drugs; subjects were divided into 3 groups: those taking traditional beta blockers (bB group), those taking third-generation beta blockers (bB-3 group), and those taking other antihypertensive drugs (non-bB group). We also enrolled subjects receiving neither antihypertensive therapy nor other chronic medication in the prior 12 months as controls. All subjects underwent personalized hypocaloric diets for a period of 24 months with monthly follow-up. Anthropometric parameters were measured at enrollment and then monthly after diet prescription. Glucose and lipid values were assessed at baseline and at 12 and 24 months during dietary regimen. Results. We enrolled a total of 120 overweight and obese patients aged 50.30 ± 1.13 years (mean ± standard deviation) with a mean BMI of 31.79 ± 0.65 kg/m2; 90 were taking antihypertensive drugs (no comorbidity and no polytherapy), while 30 subjects receiving neither antihypertensive therapy nor other chronic medication in the prior 12 months were considered as controls. After 6 months, the percent total weight loss (TWL%) was lower in the bB group (3.62 ± 1.96 versus 5.27 ± 1.76 in the bB-3 group, versus 5.15 ± 1.30 in the non-bB group, and versus 4.70 ± 0.87 in the control group), as well as their BMI. After 24 months, we kept finding the worst result in the bB group (TWL% = 9.22 ± 2.19 versus 12.79 ± 1.72 in the non-bB group and 12.28 ± 1.97 in the control group) with the best trend in the bB-3 group (TWL% = 16.19 ± 2.67).